ACTIVE MEDIA : Measurement of the gain of an optically pumped Xe2Cl active medium. (31st August 2017) - Mamaev, S B; Mikheev, L D; Polyakov, E V; Rogashevskii, A A; Shirokikh, A P; Yalovoi, V I
Abstract: We have observed for the first time the gain in a Cl2 – Xe gas mixture optically excited by radiation of a XeCl laser (308 nm), which lead to the photoassociation Xe + Cl + hv → XeCl(B, C), accompanied by the formation of a Xe2 Cl* active medium in the recombination of XeCl(B, C) with Xe. The small-signal gain at a wavelength of 532 nm in a mixture of Cl2 (1 Torr) with Xe (2 atm) is measured to be (1.1 ± 0.3) × 10 -3 cm -1 in an active volume measuring 0.5 × 1 × 80 cm for an excitation energy of 170 mJ in a pulse having a duration of 60 ns. Being recalculated to the maximum of the gain band of Xe2 Cl located at a wavelength of 504 nm, the gain amounted to (1.3 ± 0.3) × 10 -3 cm -1 . The prospects of further development of the present method for exciting the Xe2 Cl* active medium are discussed.